Answer
1. \( t x - t y + r x - r y = (t + r)(x - y) \)
2. \( b y - a x + b x - a y = (b - a)(x + y) \)
3. \( 3 a^{2} - a x + 6 a b - 2 b x = (3a - x)(a + 2b) \)
4. \( x^{3} + 3 x^{2} - x - 3 = (x - 1)(x + 1)(x + 3) \)
5. \( 2 a -1 -2 a b + b = (2a - 1)(1 - b) \)
6. \( 6 x^{2} -a y -2 a x + 3 x y = (3x - a)(2x + y) \)
7. \( 4 a^{2} - 4 b^{2} - b^{3} + a^{2} b = (a - b)(a + b)(4 + b) \)
8. \( 6 x^{2} -x^{5} -6 +x^{3} = - (x^{3} - 6)(x - 1)(x + 1) \)
9. \( x^{4} - x^{2} - x^{2} y^{2} + y^{2} = (x -1)(x +1)(x - y)(x + y) \)
10. \( x^{3} + y^{3} + x + y = (x + y)(x^{2} - xy + y^{2} + 1) \)
Solution
Let's factorize each expression step by step:
---
**1. \( t x - t y + r x - r y \)**
Factor by grouping:
\[
\begin{align*}
t x - t y + r x - r y &= t(x - y) + r(x - y) \\
&= (x - y)(t + r)
\end{align*}
\]
**Factorized Form:** \((t + r)(x - y)\)
---
**2. \( b y - a x + b x - a y \)**
Rearrange and factor by grouping:
\[
\begin{align*}
b y - a y + b x - a x &= y(b - a) + x(b - a) \\
&= (b - a)(x + y)
\end{align*}
\]
**Factorized Form:** \((b - a)(x + y)\)
---
**3. \( 3 a^{2} - a x + 6 a b - 2 b x \)**
Factor by grouping:
\[
\begin{align*}
3 a^{2} - a x + 6 a b - 2 b x &= 3a(a + 2b) - x(a + 2b) \\
&= (3a - x)(a + 2b)
\end{align*}
\end{align*}
\]
**Factorized Form:** \((3a - x)(a + 2b)\)
---
**4. \( x^{3} + 3 x^{2} - x - 3 \)**
Factor by grouping:
\[
\begin{align*}
x^{3} + 3 x^{2} - x - 3 &= x^{2}(x + 3) -1(x + 3) \\
&= (x^{2} - 1)(x + 3) \\
&= (x - 1)(x + 1)(x + 3)
\end{align*}
\end{align*}
\]
**Factorized Form:** \((x - 1)(x + 1)(x + 3)\)
---
**5. \( 2 a -1 -2 a b + b \)**
Rearrange and factor:
\[
\begin{align*}
2 a -1 -2 a b + b &= 2a(1 - b) + (b - 1) \\
&= (1 - b)(2a - 1)
\end{align*}
\end{align*}
\]
**Factorized Form:** \((2a - 1)(1 - b)\)
---
**6. \( 6 x^{2} -a y -2 a x + 3 x y \)**
Factor by grouping:
\[
\begin{align*}
6x^{2} -2a x + 3x y -a y &= 2x(3x - a) + y(3x - a) \\
&= (3x - a)(2x + y)
\end{align*}
\end{align*}
\]
**Factorized Form:** \((3x - a)(2x + y)\)
---
**7. \( 4 a^{2} - 4 b^{2} - b^{3} + a^{2} b \)**
Factor by grouping:
\[
\begin{align*}
4 a^{2} -4 b^{2} - b^{3} +a^{2} b &= a^{2}(4 + b) - b^{2}(4 + b) \\
&= (a^{2} - b^{2})(4 + b) \\
&= (a - b)(a + b)(4 + b)
\end{align*}
\end{align*}
\]
**Factorized Form:** \((a - b)(a + b)(4 + b)\)
---
**8. \( 6 x^{2} -x^{5} -6 +x^{3} \)**
Rearrange and factor:
\[
\begin{align*}
6x^{2} -x^{5} -6 +x^{3} &= -x^{5} + x^{3} + 6x^{2} - 6 \\
&= -\left(x^{5} - x^{3} - 6x^{2} + 6\right) \\
&= -\left(x^{3}(x^{2} - 1) -6(x^{2} -1)\right) \\
&= - (x^{3} - 6)(x^{2} -1) \\
&= - (x^{3} - 6)(x - 1)(x + 1)
\end{align*}
\end{align*}
\]
**Factorized Form:** \(- (x^{3} - 6)(x - 1)(x + 1)\)
---
**9. \( x^{4} - x^{2} - x^{2} y^{2} + y^{2} \)**
Rearrange and factor by grouping:
\[
\begin{align*}
x^{4} -x^{2} y^{2} -x^{2} + y^{2} &= x^{2}(x^{2} - y^{2}) -1(x^{2} - y^{2}) \\
&= (x^{2} -1)(x^{2} - y^{2}) \\
&= (x -1)(x +1)(x - y)(x + y)
\end{align*}
\end{align*}
\]
**Factorized Form:** \((x -1)(x +1)(x - y)(x + y)\)
---
**10. \( x^{3} + y^{3} + x + y \)**
Factor by grouping:
\[
\begin{align*}
x^{3} + y^{3} +x + y &= (x^{3} + y^{3}) + (x + y) \\
&= (x + y)(x^{2} -xy + y^{2}) + (x + y) \\
&= (x + y)(x^{2} -xy + y^{2} + 1)
\end{align*}
\end{align*}
\]
**Factorized Form:** \((x + y)(x^{2} - xy + y^{2} + 1)\)
---
Each expression has been fully factorized.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution